Ice geometry and thermal regime of Lyngmarksbræen Ice Cap, West Greenland - Mette Kusk Gillespie; Jacob Clement Yde; Marit Svarstad Andresen; Michele Citterio; Mark Andrew Kusk Gillespie (Journal of Glaciology)
Observations remain sparse for peripheral glaciers and ice caps in Greenland. Here, we present the results of a multi-frequency radar survey of Lyngmarksbræen Ice Cap in West Greenland conducted in April 2017. Radar measurements show thick ice of up to ~120 m in subglacial valleys associated with the largest outlet glaciers, while relatively thin ice cover the upper plateau ice divides, suggesting future vulnerability to ice cap fragmentation. At the time of the radar survey, Lyngmarksbræen Ice Cap had a total volume of 0.82 ± 0.1 km3. Measurements show a 1.5–2 m thick end-of-winter snowpack, and that firn is largely absent, signifying a prolonged period of negative mass balance for most of the ice cap. The thermal regime of Lyngmarksbræen Ice Cap is investigated through analysis of scattering observed along radar profiles. Results show that the ice cap is largely below the pressure melting point, but that temperate ice exists both in deep basal pockets and in shallow zones that some places extend from ~15 m depth and to the ice base. The distribution of shallow temperate ice appears unrelated to variations in ice thickness; instead we find a strong correlation to the presence of nearby surface crevasses.